2006
DOI: 10.4269/ajtmh.2006.74.915
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Follow-Up Interruption of Hiv Patients in French Guiana

Abstract: French Guiana is the region of France where the HIV epidemic is most prevalent. To determine the risk factors for being lost for follow-up, we followed a cohort of 1,213 patients between 1992 and 2002 and determined which variables were related to two definitions of being lost to follow-up: permanently disappearing from HIV clinics and coming back after more than 1 year of missed appointments. The incidence rate for permanent follow-up interruption was 17.2 per 100 person-years. The median time to lost to foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 2 publications
5
22
1
Order By: Relevance
“…This is consistent with studies showing that HIV-infected men are less likely to access treatment [22], [23], present with more advanced stages of HIV disease [24] and have a higher mortality risk during ART [25], [26], [27], [28], [29], [30], [31], [32]. Repeated CD4 counts were less likely in individuals under 30 years of age as also reported elsewhere[33].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with studies showing that HIV-infected men are less likely to access treatment [22], [23], present with more advanced stages of HIV disease [24] and have a higher mortality risk during ART [25], [26], [27], [28], [29], [30], [31], [32]. Repeated CD4 counts were less likely in individuals under 30 years of age as also reported elsewhere[33].…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, those who do not have regular hospital visits are associated with a high risk of self‐interruption, resulting in treatment failure . It has also been shown that younger age is a risk factor for unsuccessful clinical outcomes among HIV patients . Our study found that young patients usually visited the hospital with symptoms such as epigastralgia.…”
Section: Discussionmentioning
confidence: 58%
“…This article provides information on the constitution of the cohort and the efforts made to ensure the quality of the database, as well as the characteristics of the patients with active follow-up. Scientific studies have already been performed on this cohort [13][14][15][16][17][18][19][20][21] and several are under analysis. As a consequence of the methods of data capture and quality control, scientific analyses are possible with very short time delay.…”
Section: Discussionmentioning
confidence: 99%